calculation of limit state OF seismic irreversible metal frame buildings OF cantilever type with vertical ridge elements - L A Borodin (Structural Mechanics of Engineering Constructions and Buildings, 2010)
A method for assessing seismic irreversible skeletal systems is presented to limit state using the energy principle.